Use of Fenoldopam in Children with Congenital Heart Disease to Decrease Fluid Balance: A Retrospective, Descriptive Study and Insights into Predictors of Decreased Fluid Balance - Rausa, Jacqueline; Loomba, Rohit S.; Dorsey, Vincent; Chandra, Priya; Penk, Jamie S.; Flores, Saul; Villarreal, Enrique G.; Goldstein, Stuart L. (Journal of Pediatric Intensive Care, 2021)
This retrospective study aimed to determine if fenoldopam is associated with a decrease in fluid balance and to define the factors that may promote this in children with a history of congenital heart disease at the cardiac intensive care unit (CICU). Patients cared from January 2014 to December 2018 in the CICU were reviewed, and those on fenoldopam infusion were identified. Patient cohort data included demographics, clinical information, laboratory results, hemodynamic and urine output measurements, and information regarding fenoldopam infusion were compared between those with and without decrease in fluid balance. Forty-six patients were identified. Patients received a starting dose of fenoldopam of 0.2 mcg/kg/h, a maximum dose of 0.3 mcg/kg/h, and duration of 64 hours. Over the 4-hour study period, statistically significant change was noted in systolic pressure (decrease of 5.4%; p < 0.001), diastolic pressure (decrease of 3.5%; p = 0.01), fluid balance, and urine output (decrease of 1.3%; p = 0.027). In the cohort, 34 patients (74%) had a decrease in fluid balance, 18 (39%) had an increase in urine output, and 25 (54%) had a decrease in fluid input after the initiation of fenoldopam. Patients that had a decrease in fluid balance tended to have a higher blood urea nitrogen level at the time of fenoldopam initiation. Fenoldopam was associated with decrease in fluid balance and fluid input, but not associated with an increase in urine output. The identification of factors that can decrease fluid balance may help identify those patients who can be benefited with this treatment.
Keywords: fenoldopam; pediatrics; critical care; fluid balance; nephrology; hemodynamics